2020
DOI: 10.1371/journal.pone.0230361
|View full text |Cite
|
Sign up to set email alerts
|

Does having children increase environmental concern? Testing parenthood effects with longitudinal data from the New Zealand Attitudes and Values Study

Abstract: Having children is a transformative experience and may change the way people think about the future. Parents invest time, energy and resources to ensure the survival and reproductive success of offspring. Having children may also induce environmental concerns and investments in actions aimed at guaranteeing the quality of natural resources available to offspring. However, there is limited empirical support for this parenthood effect, and little is known about how environmental attitudes and behaviour change ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…The third finding from the study showed a close inverse relationship between parents' age and their engagement in knowledge acquisition and consumption-related behaviour. This finding is, however, not entirely supported by other empirical studies in the literature [41][42][43]. Torgler et al (2008), for example, found no visible parental age effect in terms of environmental preferences; nor did the studies by Thomas et al (2018) in the United Kingdom (UK) and Milfont et al (2020) in New Zealand, which showed that parents' age has a significant effect on their environmental behaviour.…”
Section: Discussionmentioning
confidence: 74%
“…The third finding from the study showed a close inverse relationship between parents' age and their engagement in knowledge acquisition and consumption-related behaviour. This finding is, however, not entirely supported by other empirical studies in the literature [41][42][43]. Torgler et al (2008), for example, found no visible parental age effect in terms of environmental preferences; nor did the studies by Thomas et al (2018) in the United Kingdom (UK) and Milfont et al (2020) in New Zealand, which showed that parents' age has a significant effect on their environmental behaviour.…”
Section: Discussionmentioning
confidence: 74%
“…The number of children: Women with more children showed a higher CN. In the literature, we did not identify any studies analysing the relationship between these variables, but some authors [58,59] document a positive association between motherhood and pro-environmental behaviours, expressed in sustainability and environmental protection actions. They may have eventually mediated this relationship, but it is not possible to prove this inference from our results.…”
Section: Connectedness To Nature and Demographic Variablesmentioning
confidence: 99%
“…From the 2030 Agenda and the Sustainable Development Goals [29,30], the social and educational responsibility that educational institutions have at their initial levels as essential links, together with family actions [31][32][33][34], are called upon to generate and project spaces that favour the creation of a critical citizenry committed to addressing environmental problems [31,32,35,36]. Amongst the priorities that the 2030 Agenda proposes, Sustainable Development Goal (SDG) 4 pursues a "Quality Education", specifically in Goal 4.7, which notes that, "By 2030, we must ensure all learners acquire the knowledge and skills needed to promote sustainable development, including among others, through education for sustainable development and sustainable lifestyles, human rights, gender equality, the promotion of a culture of peace and non-violence, world citizenship and the appreciation of cultural diversity, and the contribution of culture to sustainable development" [30].…”
Section: Theoretical Framework 21 Environmental Crisismentioning
confidence: 99%